Change in Work-Related Income Following the Uptake of Treatment for Mental Disorders Among Young Migrant and Non-migrant Women in Norway: A National Register Study - Hynek, Kamila Angelika; Hollander, Anna-Clara; Liefbroer, Aart C.; Hauge, Lars Johan; Straiton, Melanie Lindsay (Frontiers in Public Health, 2022)
Background: Women, and migrant women in particular, are at increased risk of many common mental disorders, which may potentially impact their labour market participation and their work-related income. Previous research found that mental disorders are associated with several work-related outcomes such as loss of income, however, not much is known about how this varies with migrant background. This study investigated the change in work-related income following the uptake of outpatient mental healthcare (OPMH) treatment, a proxy for mental disorder, in young women with and without migrant background. Additionally, we looked at how the association varied by income level. Methods: Using data from four national registries, the study population consisted of women aged 23-40 years residing in Norway for at least three consecutive years between 2006 and 2013 (N=640,527). By using a stratified linear regression with individual fixed effects, we investigated differences between majority women, descendants and eight migrant groups. Interaction analysis was conducted in order to examine differences in income loss following the uptake of OPMH treatment among women with and without migrant background. Results: Results showed that OPMH treatment was associated with a decrease in income for all groups. However, the negative effect was stronger among those with low income. Only migrant women from Western and EU Eastern Europe with a high income were not significantly affected following OPMH treatment. Conclusion: Experiencing a mental disorder during a critical age for establishment in the labour market can negatively affect not only income, but also future workforce participation, and increase dependency on social welfare services and other health outcomes, regardless of migrant background. Loss of income due to mental disorders can also affect future mental health, resulting in a vicious circle and contributing to more inequalities in the society.